A study on female final year students intention in UiTM Sarawak to become an entrepreneur / Amal Amilla Sahat and Nurul Hidayah Abdul Hai - Sahat, Amal Amilla; Abdul Hai, Nurul Hidayah (2014)
This chapter focuses the background of study which is on students’ intention to become an entrepreneur. It also emphasize merely on female final year students in UiTM Sarawak. Section 1.1 discusses the background of the study, Section 1.2 explains the problem statement and Section 1.3 states the research questions. Sections 1.4 on the other hand, states the research objectives and Section 1.5 is on the information regarding the scope of the study. In addition, Section 1.6 explains the significant of study and lastly Section 1.7 is all about definition of terms and concepts.